Interaction between the neuropeptide kyotorphin and a lipid bilayer: a constant-ph molecular dynamics study - Magalhães, Pedro Rafael da Silva Álvaro (2011)
Tese de mestrado, Bioquímica, Universidade de Lisboa, Faculdade de Ciências, 2009